The Story of Medicine: From Early Healing to the Miracles of Modern Medicine - Anne Rooney (Arcturus, 2009)
Medicine is not only a science; it is also an art. It does not consist of compounding pills and plasters; it deals with the very processes of life, which must be understood before they may be guided.' Paracelsus (1493-1541) For thousands of years, people have sought ways to overcome the diseases and disorders of the body, with methods ranging from incantations, talismans and herbal cures to antibodies, vaccines and organ transplants. The Story of Medicine charts our remarkable progress along the road of medical discovery. In a fascinating narrative, it describes the key developments and breakthroughs in our understanding of our own bodies. Topics include: . Primitive surgery - when drilling a hole in the head to let demons out was the height of surgical sophistication . Historical models of the body and disease . Dead bodies hold the key - the role of dissection in medical discovery . Diagnosis - how doctors learned to read the signs of illness . Plagues and pandemics through history . Germ theory and contagion - discovering a hidden world . How the body can turn against itself .Scarificators, leeches, maggots and other nasty treatments . Nature's pharmacopeia Detailed within these pages, too, are the stories of those who have shaped the world of medicine, including scientists, surgeons, doctors and, of course, patients.